Characterization of the Arsenate Respiratory Reductase from Shewanella sp. Strain ANA-3 - Malasarn, Davin (American Society for Microbiology (ASM), 2008)

(untitled)
Microbial arsenate respiration contributes to the mobilization of arsenic from the solid to the soluble phase in various locales worldwide. To begin to predict the extent to which As(V) respiration impacts arsenic geochemical cycling, we characterized the expression and activity of the Shewanella sp. strain ANA-3 arsenate respiratory reductase (ARR), the key enzyme involved in this metabolism. ARR is expressed at the beginning of the exponential phase and persists throughout the stationary phase, at which point it is released from the cell. In intact cells, the enzyme localizes to the periplasm. To purify ARR, a heterologous expression system was developed in Escherichia coli. ARR requires anaerobic conditions and molybdenum for activity. ARR is a heterodimer of ∼131 kDa, composed of one ArrA subunit (∼95 kDa) and one ArrB subunit (∼27 kDa). For ARR to be functional, the two subunits must be expressed together. Elemental analysis of pure protein indicates that one Mo atom, four S atoms associated with a bis-molybdopterin guanine dinucleotide cofactor, and four to five [4Fe-4S] are present per ARR. ARR has an apparent melting temperature of 41°C, a K(m) of 5 μM, and a V(max) of 11,111 μmol of As(V) reduced min(−1) mg of protein(−1) and shows no activity in the presence of alternative electron acceptors such as antimonite, nitrate, selenate, and sulfate. The development of a heterologous overexpression system for ARR will facilitate future structural and/or functional studies of this protein family.